Afterword: Social practice theory and learning work. (1st September 2016) - Martire, Anthony; Lave, Jean
Abstract: This afterword is an attempt to reframe questions about vocational education through a theory of practice concerned with the lived realities and everyday potentialities for worker/learners' learning at and through work. We briefly analyze the currents of thought in the articles in this special issue running between the critiques of the crisis in the Australian VET system and its rootedness in the structural dynamics of neoliberal economies. Following this, we offer a discussion of relations between learning and labor from the perspective of social practice theory. We suggest that reform of vocational education should start from close attention to workers learning and their collective engagements in learning/working. We argue that a theoretical perspective starting with this commitment necessarily makes very different assumptions than the behaviorist underpinnings of CBT. Much of the paper is dedicated to laying out the difference.